Entrepreneurship Education in a School - Andriadi, Dian; Idrus, Ali (Mitra Palupi, 2024)
Background: The importance of entrepreneurship education in schools and colleges is also increasingly felt in this context. With entrepreneurship education, aspiring entrepreneurs can learn how to identify market opportunities, develop business ideas and manage the company well. With entrepreneurship education, entrepreneurs can also gain knowledge about marketing strategies and financial management that will help them increase the profitability of their business. Purpose: The purpose of this study is to describe the importance of starting entrepreneurship education in schools. Design and methods: This research is field research, which is research held in a field or scene with a qualitative approach. This research was conducted at SMA 1 Merangin. Results: The implementation of entrepreneurship education in schools can be done through various creative and interactive learning methods. For example, students can be invited to make a simple business plan, take part in a business simulation, or make visits to local companies. In addition, teachers can also invite successful entrepreneurs as guest speakers to share their experiences and knowledge. entrepreneurship education programs in schools have significant positive impacts. The evaluation conducted helps in identifying the weaknesses of the program and provides direction for necessary improvements.